The Ozaki procedure with cardioCel patch for children and young adults with aortic valve disease: preliminary experience - a word of caution - Chivers,SC; Pavy,C; Vaja,R; Quarto,C; Ghez,O; Daubeney,PEF (World Journal for Pediatric and Congenital Heart Surgery, 2019)
Background:The Ozaki procedure is a surgical technique for patients with significant aortic stenosis or regurgitation or both where valve repair cannot be performed. Individual cusps are cut from glutaraldehyde-treated autologous pericardium or bovine pericardium and implanted into the aortic valve position. Encouraging results have been reported within the adult population. There are limited published data on success of this procedure in younger patients.Methods:We present a series of five children and young adults who underwent the Ozaki procedure with neoaortic valve cusps made from CardioCel, a decellularized bovine pericardial patch treated with a monomeric glutaraldehyde.Results:There were no complications in the initial postoperative period and short inpatient stay. At a mean follow-up of 29.6 months (range: 22-36 months), 4 patients had no evidence of stenosis and 3 patients had trivial or no regurgitation from the neoaortic valve. Overall, two patients had complications related to the valve and underwent reintervention during the follow-up period with a Ross procedure. One of these patients who was not taking long-term anticoagulation experienced a transient ischemic attack.Conclusions:Our experience demonstrates that the Ozaki procedure with CardioCel in pediatric and young adult patients should be approached with caution. Further research with larger groups of pediatric patients, comparison of different graft materials, and longer follow-up is required to ascertain long-term success in children.